Analisis Produktivitas Unit Produksi di Perusahaan Abon UD Sumber Hasil Malang dengan Menggunakan Metode Objective Matrix (Omax) - Richard Sijoatmodjo; Yuswono Hadi (Teknik Industri Universitas Ma Chung, 2021)
This study focuses on the importance of high productivity in companies' production processes and its impact on profits. The study uses the Omax method to measure productivity in a company's production process. The Omax method is based on four variables: the amount of meat used, the amount of beans used, the amount of electricity used, and the amount of labor used. The study found that higher productivity leads to higher profits, and companies can use the Omax method to measure their productivity level and improve their production processes. The study's results show that the average Productivity Index (PI) for 24 observation periods is 3.151667, with the lowest PI value being 1 and the highest being 5.79. Companies can follow the proposed calculation procedure to determine the productivity level of their production unit using the Omax method. Overall, the study emphasizes the importance of measuring productivity and using appropriate methods to improve production processes to achieve higher profits.